A novel approach with modified suture bridge fixation technique for posterior cruciate ligament tibial avulsion fracture in adult - Wang, Xiong; Gu, Qing; Zi, Shuming; Wei, Wenqiang; Cheng, Biao; Cao, Liehu (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundPosterior cruciate ligament (PCL) tibial avulsion fractures are relatively rare injuries that often result in chronic pain, limited range of motion, knee instability, and osteoarthritis. Most cases require surgical intervention to restore the fragment’s normal anatomy, the ligament’s tension, and the knee joint’s stability. In this study, we propose a novel approach utilizing a modified suture bridge fixation technique to treat PCL tibial avulsion fractures and explore the clinical outcome and applicability.MethodsWe retrospectively reviewed and collected the clinical data from March 2020 to April 2023. Of the 24 patients (14 males and 10 females) with PCL tibial avulsion fractures who underwent modified suture bridge fixation technique were enrolled in the study. The surgical data of the surgery time and intraoperative blood loss were analyzed. The knee range of motion (ROM), the Lysholm knee scoring scale, and the International Knee Documentation Committee (IKDC) were used to evaluate the recovery of knee joint function.ResultsAll 24 patients were followed up for a duration ranging from 11 to 16 months, with an average of 13.00 ± 1.32 months. The surgery time was 40∼60 min, with a mean of 50.88 ± 4.85 min. The intraoperative blood loss was approximately 25∼45 mL, averaging 36.75 ± 4.89 mL. No instances of wound infection, neurovascular injuries, fracture nonunion, fixation failure, deep vein thrombosis, or secondary operation were reported during follow-up. The knee joint range of motion (ROM) was 118°∼134°, with an average of 127.46° ± 4.16° at the final follow-up. The Lysholm score was 41.17 ± 3.48 at the preoperative stage and improved to 90.25 ± 2.59 at the final follow-up. The IKDC score was 40.38 ± 2.16 at the preoperative stage, and 88.54 ± 1.77 at the final follow-up.ConclusionThe results indicate that the novel approach utilizing a modified suture bridge fixation technique can provide effective stabilization and favorable clinical outcomes. The suture bridge structure can be applied to displaced posterior cruciate ligament (PCL) tibial avulsion fractures through its compression capabilities, especially in comminuted fractures. This procedure is straightforward, minimizing the risk of injury to peripheral neurovascular structures and eliminating the need for a second operation. Consequently, this technique represents a viable alternative treatment option for primary care facilities or hospitals that lack arthroscopic equipment.